2020
DOI: 10.1200/jgo.19.00340
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Immunochemical Test as a Screening Method for Colorectal Cancer in University College Hospital Ibadan, Nigeria

Abstract: PURPOSE Colorectal cancer (CRC) is a disease of public health importance because of the increasing incidence of the disease and presentation in advanced stage of the disease in Western Africa. CRC is amenable to screening because of the long course of premalignant lesions before final development of the disease. Despite this, the practice of CRC screening is inadequate at the sites in this study. The fecal immunochemical test (FIT) is one of the recommended noninvasive methods for CRC screening. It has a sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In particular, religion strongly impacts how people relate to health care and medicine, and physician consultations upon initial symptom presentation are not typical [ 18 ]. A similar cultural attitude is found in Nigeria [ 25 ] and Egypt [ 23 ].…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…In particular, religion strongly impacts how people relate to health care and medicine, and physician consultations upon initial symptom presentation are not typical [ 18 ]. A similar cultural attitude is found in Nigeria [ 25 ] and Egypt [ 23 ].…”
Section: Resultssupporting
confidence: 73%
“…Knapp et al [ 24 ] also mentioned that 100% of participants who completed the test kit reported a willingness to undergo colonoscopy if it was free (~90% with a positive FIT result underwent follow-up colonoscopy). The follow-up colonoscopy rates in the other studies were much lower, ranging from 18% to 66% [ 22 , 25–27 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…A prospective, multi-center, Nigerian study of 362 patients with a recent history of self-reported rectal bleeding documented an ADR of 8.2%, despite a CRC prevalence of 18.2% (66/362) [ 27 ]. In a recent prospective study from the University College Hospital in Ibadan, Nigeria, the ADR was 9.1% among asymptomatic adults undergoing CRC screening [ 28 ]. A lower proportion of traditional adenomas may decrease FIT performance as the sensitivity of the test is inferior for non-adenomatous polyps (e.g.…”
Section: Discussionmentioning
confidence: 99%